ANALISIS STRATEGI PEMASARAN SUROBOYO CARNIVAL NIGHT MARKET DI KOTA SURABAYA, PROVINSI JAWA TIMUR - Avichena, Ibnu; Anom, I Putu; Sukana, I Made (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2016)
The business competition of man made tourism industry especially at East Java Province is quite tight. One of them is Surabaya City that has Suroboyo Carnival Night Market (SCNM) as the newest man made tourist attraction which in the past year has been the favourite of local tourist in Surabaya. The research conducted in SCNM that focused on external conditions of SCNM, internal conditions of SCNM are viewed through the marketing mix, and review the implementation of SCNM marketing strategy which are analyzed by online reviews of SCNM visitors in Trip Advisor website. The data type are qualitative and quantitative data. Data are collected by observation, interview, documentation, and literature review. The informants are selected by purposive sampling method. Then descriptive qualitative analysis used to analyzing the data. This study shows that the external conditions of SCNM are influenced by politic factor, economy factor, social factor, and technology factor that each of it has opportunities and threats. The internal conditions of SCNM are viewed from product aspect has a diverese rides, from pricing aspect has an affordable price, from promotion aspect offers a variety of interesting promo, from place aspect is zero level channel, from people aspect is still hampered by the lack of employee that certified regional competency standards, from process aspect has in-out area, playground and public area, and night market area, from physical evidence aspect has a highly characteristic through their decoration and their souvenirs. SCNM marketing strategy was also quite successful by gaining 77.5% points good reviews from visitors based on the Trip Advisor website.
Keywords: SCNM, Marketing Mix, Online Review